The Effect of Fiscal Decentralization on Economic Development Performance in Indonesia - Muhamad Armawaddin; Wali Aya Rumbia; Ahmad Ahmad (Universitas Negeri Malang, 2022)
The purpose of this study is to test and analyze the influence of fiscal decentralization on development performance in Indonesia using the structural equation model approach. The data uses panel data, from 34 provinces and in 2015-2019 sourced from the Ministry of Finance of the Republic of Indonesia and the Central Bureau of Statistics (BPS). Data analysis using structural equation model approach with the help of Smart-PLS 3.3.3 software. The outer model evaluation results concluded that all indicators of fiscal decentralization variables and economic development performance variables are valid. The most powerful indicator reflecting the latent variable of fiscal decentralization is the ratio of regional income and economic development performance is an indicator of economic growth. The results of the evaluation of the inner model found that fiscal decentralization performance has a positive and significant influence on development performance. The existence of fiscal inequality among provinces in Indonesia causes uneven ratios of capital expenditures and public incomes as seen from the low indicator in reflecting decentralization of fiscal and economic performance